Cytotoxicity and antibacterial activities of plant-mediated synthesized zinc oxide (ZnO) nanoparticles using Punica granatum (pomegranate) fruit peels extract - Siti Nur Amalina, M. S.; Shameli, Kamyar; Wong, Magdelyn Mei Theing *; Teow, Sin Yeang *; Chew, Jactty *; Nur Afini, I. (Elsevier, 2019)
The unique properties of zinc oxide nanoparticles (ZnO-NPs) produced using plant extract make them attractive for use in medical as well as industrial applications, and it is necessary to develop environmentally friendly methods for their synthesis. This can be accomplished by replacing the traditional chemical compounds for the reduction of the zinc ions to ZnO-NPs during synthesis with natural plant extracts. Here, the biosynthesis of ZnO-NPs using Punica granatum (P. granatum) fruit peels extract was investigated as the reducing and stabilizing agent. The P. granatum/ZnO-NPs with spherical and hexagonal shapes were biosynthesized at different annealing temperatures. The X-ray diffraction analysis confirmed the synthesis of highly pure ZnO-NPs with increasing crystallinity in higher annealing temperatures. The ZnO-NPs displayed characteristic absorption peaks between 370 and 378 nm in the UV–vis spectra. Transmission electron microscopy (TEM) imaging showed the formation of mostly spherical and hexagonal-shaped ZnO-NPs in the mean size of 32.98 nm and 81.84 nm at 600 °C and 700 °C respectively. According to FTIR spectrum, strong absorption bands in the range of 462–487 cm−1 corresponding to ZnO bond stretching can be seen. Antibacterial activities of P. granatum/ZnO-NPs against Escherichia coli (E. coli) and Enterococcus faecalis (E. faecalis) were investigated and compared. Results obtained show that smaller-sized P. granatum/ZnO-NPs are more effective in inhibiting growth of both bacteria. In addition, cytotoxicity assays were performed for P. granatum/ZnO-NPs against human colon normal and cancerous cells. P. granatum/ZnO-NPs exhibited similar killing activities of both cell lines at the concentration of ≥31.25 μg/mL. The biosynthesized ZnO-NPs could offer potential applications in bio-medical field.